Akademi Kebidanan Di Rokan Hilir Dengan Pendekatan Arsitektur Tropis - Putra Mhd Alamsyah; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Health development is one of the main factors to promote an area. If an area in the field of health is good, then the rate of progress and human resources will also improve. One factor that is still ahealth problem in Indonesia is still high mortality rate of mothers and children. This is due to the lack of public knowledge in the world of health, especially in terms of delivery was also afterpostpartum. To support the achievement of the Vision Riau Province in health in the form of